Waist circumference and abdominal volume index are the strongest anthropometric discriminators of metabolic syndrome in Spanish adolescents (2019)
Background: Waist circumference has been suggested as predictor for metabolic syndrome (MetS) in adolescents but it has not been compared with newly proposed anthropometric indexes. This study aimed to disclose the capacity of ten classic and novel anthropometric indexes to discriminate by the presence of MetS in this young population. Materials and methods: A cross-sectional study was performed on 981 adolescents (13.2 ± 1.2 years) randomly recruited from eighteen schools in south-east Spain. Body fat percentage (BF%), abdominal volume index (AVI), body roundness index (BRI), body mass index (BMI), body adiposity index (BAI), body adiposity index for paediatrics (BAIp), conicity index (C-Index), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and body shape index (ABSI) were measured and calculated. Receiver-operator curves (ROC) were created to determine the discriminatory capacity of these anthropometric parameters for MetS. Results: The prevalence of MetS was 7.0% for boys and 6.1% in girls. Participants with MetS had significantly higher levels of blood pressure and plasma levels of lipids, glucose and insulin. All anthropometric indexes were elevated in MetS individuals compared to the non-MetS group. AVI and WC showed the highest AUC values (0.83 for boys and 0.86 for girls). In contrast, according to ROC analyses, no anthropometric index was capable of discriminating the components of MetS (hypertension, hypertriglyceridemia, hyperglycaemia and low-HDL levels), except for abdominal obesity. Conclusion: We suggest the use of WC and AVI, with the cut-off points presented herein, for the discrimination between adolescents with or without MetS. © 2018 Stichting European Society for Clinical Investigation Journal Foundation